Pengaruh Reward dan Komunikasi Terhadap Produktivitas Kerja Karyawan SPBE PT. Mitra Buana Energi Raya - Daniel Fauzia Sandi; Rita Tri Yusnita; Titin Patimah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This research aims to determine the simultaneous and partial influence of Reward and Communication on Employee Work Productivity at SPBE PT. Mitra Buana Energi Raya. The research method used in this research is quantitative research methods with a census approach. The population in this study were employees of the SPBE operator PT. Buana Energi Raya partners are 45 people. The type of data used in this research is primary data obtained through a questionnaire. The data testing technique used in this research uses validity tests, reliability tests and classical assumption tests. Data analysis in this research uses multiple regression analysis tools using SPSS version 25 software. The results of the research show that Rewards and Communication simultaneously have a significant effect on Employee Work Productivity at PPBE PT. Mitra Buana Energi Raya. Rewards partially have a significant effect on employee work productivity at SPBE PT. Mitra Buana Energi Raya. Communication partially has a significant effect on employee work productivity at PBE PT. Mitra Buana Energi Raya.